Puncturing the waterbed or the new green paradox? The effectiveness of overlapping policies in the EU ETS under perfect foresight and myopia - Lukas Schmidt (Institute of Energy Economics at the University of Cologne (EWI), 2020)
The latest reform of European Union Emission Trading System (EU ETS) enables overlapping policies, such as national coal phase-outs, to affect total emissions. For evaluatingoverlapping policies, this paper applies a detailed partial equilibrium model of the EU ETS.Under perfect foresight, overlapping policies decrease total emissions if implemented earlyon. Though, endogenous cancellation within the EU ETS mitigates the waterbed effecthardly by more than 50%. In contrast, overlapping policies mostly do not affect total emissions significantly or even increase them via the new green paradox effect if implementedlate and firms anticipate their long-term impact. If overlapping policies focus on low-costabatement options, they become more effective in mitigating the waterbed effect, with aneffectiveness of up to 60%. The effectiveness of overlapping policies decreases if firms aremyopic. Myopia also increases the danger of the new green paradox effect for early implemented overlapping policies. However, the absolute increase in total emissions via thenew green paradox remains below a third of today's yearly emissions if overlapping policiespermanently reduce allowance demand by 10%.
Keywords: C61; H23; Q48; Q58; 330; Intertemporal Emission Trading; Overlapping Policies; EU ETS; New Green Paradox; Marginal Abatement Costs; Myopia